PERAN SHOPPING ENJOYMENT MEMEDIASI PENGARUH HEDONIC MOTIVATION TERHADAP IMPULSE BUYING - Darmaningrum, Putu Cindy Clarista; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 8 No 6 (2019)DO - 10.24843/EJMUNUD.2019.v08.i06.p17, 2019)
The purpose of this study is to explain the role of enjoyment shopping mediating hedonic motivation towards impulse buying. This research was conducted at consumers of Stradivarius Beachwalk. The measure of samples used in this study were 105 respondents, with a purposive sampling method. Data collection is done through questionnaires, interviews, and observations. The analysis technique used is path analysis. Based on the results, it was found that shopping enjoyment is able to mediate partially hedonic motivation towards impulse buying. Furthermore, hedonic motivation has a positive and significant effect on impulse buying; hedonic motivation has a positive and significant effect on shopping enjoyment; shopping enjoyment has a positive and significant effect on impulse buying; and shopping enjoyment acts as a mediating variable between hedonic motivation and impulse buying. Based on the findings of this study suggested that hedonic motivation and good shopping enjoyment greatly affect consumer impulse buying at Stradivarius Beachwalk. Keywords: hedonic motivation, shopping enjoyment, impulse buying